Effect of tillage and crop sequences on arbuscular mycorrhizal symbiosis and soil enzyme activities in soybean (Glycine max) rhizosphere - SHARMA, MAHAVEER P; GUPTA, SONAM; SHARMA, SHUSHIL K; VYAS, A K (The Indian Journal of Agricultural Sciences, 2012)
The aim of present study was to evaluate the impact of tillage practices and crop sequences on AM fungal propagules, infectivity potential and soil enzyme activities in the soybean rhizosphere of a long-term field trial maintained since 2001. Rhizosphere soil and root samples of soybean were drawn in kharif 2008 from three tillage systems (conventional- conventional (C-C), conventional-reduced (C-R) and reduced-reduced (R-R) and four soybean-based crop rotations (soybean–wheat (S–W), soybean–wheat–maize–wheat (S–W–M–W), soybean–wheat–soybean–wheat–maize–wheat (S– W–S–W–M–W) and soybean+ maize-wheat (S+M–W) which are being maintained in split plot design for the past seven years. On completion of six cropping seasons, significantly higher mycorrhizal spore count (17.0/g soil) and infectivity potential (IP) (4.58 IP/g soil) were observed in soybean grown under S–W–M–W rotation under C-R tillage system. However, the per cent root length colonized by AMF was found highest (12.66%) in S+M–W rotation under C-R tillage system. In general, the S+M–W or S–W–M–W rotations under R-R tillage system showed higher soil dehydrogenase activity (3.96 pKat/g soil) and fluorescein diacetate hydrolytic activity (110.76 pKat/g soil) when compared to other combinations. The inclusion of maize in the rotation irrespective of tillage systems showed comparatively higher phosphatase activities. Higher soybean grain yield (3 008 kg/ha) although not significantly higher was recorded in S+M–W rotation under C-C tillage, followed by same rotation (2 814 kg/ha) under C-R tillage system when compared to all other combinations. Moreover, IP of resident AM fungi in soybean rotation involving maize in conservation tillage was found to be highly correlated (r=0.96 to 0.99) with grain yield of soybean and maintaining higher organic carbon which indicates the functioning of resident AM fungi in enhancing the soybean yield.